High-performance Countercurrent Chromatography to Access Rhodiola rosea Influenza Virus Inhibiting Constituents - Langeder, Julia; Grienke, Ulrike; Döring, Kristin; Jafari, Mahtab; Ehrhardt, Christina; Schmidtke, Michaela; Rollinger, Judith M. (Planta Medica, 2020)
In a cytopathic effect inhibition assay, a standardized Rhodiola rosea root and rhizome extract, also known as roseroot extract (SHR-5), exerted distinct anti-influenza A virus activity against HK/68 (H3N2) (IC50 of 2.8 µg/mL) without being cytotoxic. For fast and efficient isolation and identification of the extractʼs bioactive constituents, a high-performance countercurrent chromatographic separation method was developed. It resulted in a three-stage gradient elution program using a mobile phase solvent system composed of ethyl acetate/n-butanol/water (1 : 4 : 5 → 2 : 3 : 5 → 3 : 2 : 5) in the reversed-phase mode. The elaborated high-performance countercurrent chromatographic method allowed for fractionation of the complex roseroot extract in a single chromatographic step in a way that only one additional orthogonal isolation/purification step per fraction yielded 12 isolated constituents. They cover a broad polarity range and belong to different structural classes, namely, the phenylethanoid tyrosol and its glucoside salidroside, the cinnamyl alcohol glycosides rosavin, rosarin, and rosin as well as gallic acid, the cyanogenic glucoside lotaustralin, the monoterpene glucosides rosiridin and kenposide A, and the flavonoids tricin, tricin-5-O-β-D-glucopyranoside, and rhodiosin. The most promising anti-influenza activities were determined for rhodiosin, tricin, and tricin-5-O-β-D-glucopyranoside with IC50 values of 7.9, 13, and 15 µM, respectively. The herein established high-performance countercurrent chromatographic protocol enables fast and scalable access to major as well as minor roseroot constituents. This is of particular relevance for extract standardization, quality control, and further in-depth pharmacological investigations of the metabolites of this popular traditional herbal remedy.
Keywords: high-performance countercurrent chromatography; Rhodiola rosea; Crassulaceae; influenza virus; human rhinovirus; antiviral